Edukasi Kesehatan Pencegahan Demam Berdarah Dengue pada Siswa SDN 02 Panduman, Desa Jelbuk, Kabupaten Jember - Senjarini, Kartika; Wathon, Syubbanul; Oktarianti, Rike (Politeknik Negeri Jember, 2025)
Dengue hemorrhagic fever (DHF) remains a major public health concern in tropical and subtropical countries, including Indonesia. School-aged children are among the most vulnerable groups due to limited awareness and daily habits that may support mosquito breeding. This community service activity aimed to enhance students’ knowledge of DHF prevention through health education at SDN 02 Panduman, Jelbuk Village, Jember Regency, East Java Province. Educational interventions were delivered interactively using PowerPoint presentations, posters, ovitrap demonstrations, videos, and pocketbooks adapted to the comprehension level of elementary school students. The evaluation was conducted using pre-test and post-test questionnaires consisting of 10 multiple-choice questions on dengue transmission, symptoms, and prevention. The results showed a significant improvement in student knowledge (25%), with average scores increasing from 63% to 88% (p < 0.001, Wilcoxon test). The distribution of illustrated pocketbooks served as an effective reinforcement tool, allowing students to share knowledge with their families and communities. Overall, the intervention successfully raised awareness and fostered preventive behavior among students, demonstrating that school-based health education is an effective strategy for reducing the risk of DHF transmission in endemic rural areas such as Jelbuk Village.